High Temperature Heat Damage Grade Index of Tea Plants and Its Distribution Characteristics in Southern Yangtze River and South China - Li Xin; Wang Peijuan; Tang Junxian; Wang Qi; Li Yang; Huo Zhiguo (应用气象学报)
With the trend of global climate change, it is important to study the high temperature heat damage of tea plants and analyze the spatial and temporal distribution characteristics to warn damage early and reduce production losses. An index is established based on daily maximum air temperature and historical heat damage disaster records at 510 meteorological stations over tea regions in Southern Yangtze River and South China from 1961 to 2022, to determine and verify the extent of high temperature heat damage, using methods of disaster inversion and K-means clustering analysis method. The spatial and temporal distribution characteristics of high temperature heat damage are analyzed. The total days with moving average of 14-consecutive-day maximum temperature above 34.5 ℃ are statistically analyzed, and for mild, moderate and severe high temperature heat damage, the value is in the range of 1-17 d, 18-38 d and above 38 d, respectively. The accuracy rate of complete compliance with the validation sample is 73.9%, and the accuracy rate of basic compliance is 91.3%. The total number of heat damage on tea plants in Southern Yangtze River and South China shows fluctuating changes from 1961 to 2022. The total number of heat damage on tea plants in tea regions of Southern Yangtze River and South China is the lowest in 1999 and 1997, respectively, while numbers are the highest in 2021 for both tea regions. Compared to tea regions of Southern Yangtze River, there are more high temperature heat damages in South China, especially mild high temperature heat damages. Moreover, the number of high temperature heat damage on tea plants in South China shows a significant increasing trend in the past 62 years, but the trend of changes in the number of high temperature heat damage on tea plants in most tea regions of Southern Yangtze River is not significant.